SOSIALISASI PENERAPAN CARA PEMBENIHAN IKAN YANG BAIK (CPIB) DAN VAKSINASI PADA KOMODITAS IKAN NILA DI KAMPUNG NILA KAWALI, CIAMIS - Pramono Adi, Catur (JURNAL KASTARA, 2024)
The application of Good Fish Seedling Practices (GFSP) is critical, as proper broodstock management has a direct impact on enhanced fish output. Furthermore, inoculation with the Triptovac-22 vaccine, created by Marine and Fisheries Polytechnic of Karawang Polytechnic, is used to protect broodstock and produce disease-resistant progeny. This effort intends to: (1) adopt standardized immunization techniques; (2) examine the issues faced by fish farmers during GSFP implementation; and (3) increase tilapia farmers' production and income. The activity produced positive outcomes, including: (1) interactive discussions with tilapia farmers on adhering to GSFP standards in their aquaculture practices; (2) knowledge transfer on fish vaccination to the community; (3) fostering an understanding within the Fish Farmers Group on the importance of fish vaccination; and (4) identifying the lack of public awareness regarding hygienic water.